MANAJEMEN PROYEK MODERN : MEMANFAATKAN TOOLS DIGITAL UNTUK EFISIENSI MAKSIMAL - Dodi Setiawan Riatmaja; Windy Wonmaly; Firman Gazali Djunaidi; Adhi Indra Hermanu; Muhammad Arif Abdul Hakim; Abraham Manuhutu (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Modern project management has undergone a significant transformation along with the advancement of digital technology. Digital tools, such as project management software, collaboration apps, and cloud-based technologies, are now crucial elements in improving team efficiency and productivity. This article reviews how the utilization of digital tools can help plan, execute, and evaluate projects more effectively. With case studies and application examples, this research shows that technology adoption not only accelerates project completion but also minimizes risks and errors. The results of this analysis confirm the importance of technology integration in modern project management to face the challenges of increasingly complex and fast-changing business dynamics.